1991
DOI: 10.1159/000293131
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Duration of Fetal Breathing Movements and Gestational Age and the Development ofthe Central Nervous System at 25–32 Weeks of Gestation in Normal Pregnancy

Abstract: In 15 pregnant women with normal pregnancy at 25–32 weeks of gestation, fetal breathing movements (FBM), fetal body movements and fetal heart rate were continuously and simultaneously recorded over a total period of 180 min. The frequency of successive FBM with a duration < 10 s (apnea period > 3 s) showed a significant decrease (p < 0.01), while the frequency of successive FBM with a duration ≥ 30 s showed a significant increase from 25 to 32 weeks of gestation (p < 0.001). Strong positive correlations were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
2
0
4
Order By: Relevance
“…It was demonstrated that there was a signifi cant correlation between the maturation of the fetal breathing pattern and the incidence of neonatal respira tory complications in 121 pregnancies. However, only 40 of the patients studied were women who had premature delivery, and we have recently found that the frequency of successive breathing movements with a duration of 30 s or more shows a significant increase as pregnancy advances [9], In the present study, we, therefore, classi fied fetal breathing patterns into three types according to the presence or absence of breathing movements and the duration of successive respiratory movements. Only pregnant women who eventually underwent preterm birth were chosen as subjects.…”
Section: Introductionmentioning
confidence: 90%
“…It was demonstrated that there was a signifi cant correlation between the maturation of the fetal breathing pattern and the incidence of neonatal respira tory complications in 121 pregnancies. However, only 40 of the patients studied were women who had premature delivery, and we have recently found that the frequency of successive breathing movements with a duration of 30 s or more shows a significant increase as pregnancy advances [9], In the present study, we, therefore, classi fied fetal breathing patterns into three types according to the presence or absence of breathing movements and the duration of successive respiratory movements. Only pregnant women who eventually underwent preterm birth were chosen as subjects.…”
Section: Introductionmentioning
confidence: 90%
“…It has been shown from the observations made over 24 hr that at 24-28 weeks of gestation, fetuses breathe about 14 % of the time [16] and by 34 to 40 weeks breathing increases to about 30% of the time [17]. From 25 to 32 weeks, episodes of shorter breaths decrease and those lasting for more than 30 s increase [18]. Episodic breathing is interspersed with apnoeic periods whose duration varies with the gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque la coincidencia de una señal con complejos QRS fetales con una relación señal a ruido apropiada y la presencia de MRF por periodos mayores a 4.6. Limitaciones 42 30s restringieron el número final de casos disponible para análisis, esa ventana de tiempo elimina diferencias potenciales que pudieran influir debido a la maduración o al estado fetal [107]. En consecuencia, se analizó un grupo muy selecto en términos de edad gestacional (32-37 semanas), peso estimado (< percentil 3) e índices hemodinámicos, y fue posible estudiar como es que la ASR modifica a la frecuencia cardiaca durante los MRF en el caso específico de RCF sin alteraciones hemodinámicas Doppler.…”
Section: Limitacionesunclassified
“…Se analizó el vector de tiempos de MRF con el fin de localizar segmentos de 30 s con presencia de movimientos respiratorios. Esta duración se estableció con base en el desarrollo del sistema nervioso central de fetos sanos, como sugirió Higuchi et al [107], y de igual forma procurando mantener el mismo intervalo [143]. De esta forma se generó un nuevo vector de tiempos con base en la ubicación temporal de los fotogramas correspondientes a cada inicio inspiratorio dentro del segmento estudiado.…”
Section: Preprocesamientounclassified
See 1 more Smart Citation